Penyuluhan kesehatan tentang penyakit hipertensi pada lansia - Adilla Nesya Putri; Sri Suharti (Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2021)
Hypertension is defined by the Joint National Committee on Detection (JIVC) as a pressure higher than 140/90 mmHg and is classified according to its degree of severity, ranging from normal high blood pressure (BP) to malugary hypertension. Hypertension is categorized as mild when the diastolic pressure is between 105 and 114 mmHg. And severe hypertension when the diastolic pressure is 115 mmhg or more. The goal of hypertension counseling is to increase the knowledge of the elderly about the dangers of hypertension, the importance of pandemic and the dangers if the home with health protocol during the Covid 19 pandemic and the dangers if the home environment is no clean.Participants who attended were 6 people. The place used is in accordance with the plan that was made using the equipment during outreach such as flipcharts and leaflets. The result of this activity can increase the knowledge of the elderly about hypertension .